2001
DOI: 10.1046/j.1442-200x.2001.01474.x
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant protein (SP) B associations and interactions with SP‐A in white and black subjects with respiratory distress syndrome

Abstract: Background-The etiology of respiratory distress syndrome (RDS) is multifactorial and/or multigenic. Surfactant protein A (SP-A) and/or SP-B genetic variants have been identified as risk or protection factors for RDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
74
2
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 25 publications
4
74
2
2
Order By: Relevance
“…Regarding the protection against the development of the disease, it was evident both in the heterozygous C/T and homozygous T/T genotype. The authors suggested that the genotype T/T seem to increase the protection in relation to the disease, as was demonstrated with the black patients with RDS by Floros et al 56 In a study conducted in Finland, the genotype C/C of the polymorphism C/T 1580 seemed to constitute both a risk factor for the alleles of SP-A for susceptibility to RDS and a protective factor for the allele 6A3. 60 Guo et al showed that the allele C seemed to be associated with a high risk of chronic obstructive pulmonary disease.…”
Section: Genetic Factors Of Respiratory Distress Syndromementioning
confidence: 78%
See 4 more Smart Citations
“…Regarding the protection against the development of the disease, it was evident both in the heterozygous C/T and homozygous T/T genotype. The authors suggested that the genotype T/T seem to increase the protection in relation to the disease, as was demonstrated with the black patients with RDS by Floros et al 56 In a study conducted in Finland, the genotype C/C of the polymorphism C/T 1580 seemed to constitute both a risk factor for the alleles of SP-A for susceptibility to RDS and a protective factor for the allele 6A3. 60 Guo et al showed that the allele C seemed to be associated with a high risk of chronic obstructive pulmonary disease.…”
Section: Genetic Factors Of Respiratory Distress Syndromementioning
confidence: 78%
“…36 In 2001 Floros et al conducted a case-control study with preterm newborns with and without RDS. 56 The authors concluded that the genotype A/G of the polymorphism A/ G 9306 seems to be a susceptibility factor for RDS in individuals with gestational age greater than or equal to 33 weeks. The presence of specific alleles of SP-A and SP-B in the same individual resulted in a considerable change of the values of P or odds ratio, when compared to the values obtained with each genotype separately.…”
Section: Genetic Factors Of Respiratory Distress Syndromementioning
confidence: 98%
See 3 more Smart Citations